The Roots of Canadian Law in Canada - Saul, John (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractThis article asks the Canadian legal community to look beyond the standard historical viewpoint that roots Canadian law in the British common law and French civil law traditions. The author discusses the historical foundations of Canadian law in a uniquely Canadian context, beginning with the earliest interactions between the First Nations and the Europeans. Drawing on the research outlined in his recent book, A Fair Country, the author challenges his audience to think of Canadian law as far more than the local implementation of foreign legal traditions. While Canada has freely borrowed from various legal traditions, the application of law in Canada has been a unique process intimately tied to Canadian history. The author calls on us to recognize a distinctly Canadian legal tradition which has grown out of Aboriginal law and subsequent local experience while being influenced by, but by no means limited to, common law and civil law traditions.